MARGINALIZATION OF KHITBAH IN LOMBOK MUSLIM MARRIAGE IN WEST NUSA TENGGARA - Hasbi Assyiddiqi Hasbi; Abdullah (Al-IHKAM Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2024)
This study examines the first, is it true that there is marginalization of khitbah in the pre-marital process of Lombok Muslim society, second, what is the philosophical basis that causes this marginalization. Third, what are the alternative solutions so that khitbah can be applied in the midst of Muslim society as a pre-marital process. The research data includes primary data and secondary data, primary data obtained from respondents, informants and informants, in collecting data this research used interview and documentation techniques and then analyzed using a deductive method. This study found that sermons were indeed marginalized, this was evidenced by the implementation of khitbah only reaching 42% and 58% did not use khitbah, the marginal philosophical basis of sermons was 59% due to culture, 22% due to economic factors, 14% due to age and 5% due to social factors. law. Alternative solutions to this problem require the active role of religious leaders and community leaders in campaigning for the important role of khitbah and the government needs to establish more binding regulations.